Canagliflozin-associated severe hyponatremia: a rare and potentially adverse effect?. (30th March 2022) - Dhanasekaran, Maheswaran; Narayanan, Siddharth; Mastoris, Ioannis; Mehta, Suchita
Abstract : Summary: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) induce osmotic diuresis by inhibiting the proximal renal tubular reabsorption of the filtered glucose load, which in turn can occasionally lead to severe dehydration and hypotension amidst other adverse effects. We present a case of a 49-year-old man with type 2 diabetes mellitus (T2D) on canagliflozin, a SGLT2i. The patient was brought to the emergency room following a motor vehicle accident. He was confused and had an altered mental status. His blood alcohol and urine toxicology screens were negative. Initial investigations revealed that he had severe hyponatremia with euglycemic ketoacidosis. The adverse condition was reversed with close monitoring and timely management, and the patient was eventually discharged. This is the first report to suggest hyponatremia as a potentially serious adverse effect following SGLT2i therapy. Its impact on the renal tubule handling of sodium and water is not yet well characterized. While further studies are warranted to understand better the pathophysiological mechanisms associated with SGLT2i-induced adverse effects, timely dose reduction or perhaps even its temporary discontinuation may be recommended to prevent complications. Learning points: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are usually well-tolerated, but some serious adverse effects have been documented. Our case report suggests hyponatremia as a potential, rare side effect of SGLT2i and makes physicians aware of the occurrence of such life-threatening but preventable complications. Timely and close monitoring of the patient, with temporary discontinuation of this drug, may be recommended towards effective management. Studies demonstrating a comprehensive understanding of SGLT2i-related electrolyte derangements are warranted.